"To hit, or not to hit?" Examining the similarity between practice and real swings in golf - Carson, H. J.; Collins, D.; Richards, J. (International Journal of Golf Science, 2014)
Practice swings are commonly employed among golfers, presumably based on the tacit assumption that they share common psychomotor processes with real swings; however, this has not been verified by empirical research. Therefore, this study aimed to examine whether practice swings shared equivalent levels of control to real golf swings, when attempting the same target behavior. Three PGA Professional golf coaches and six amateurs (mean handicap = 2.7, SD = 2.2) each executed 20 swings under two quasirandom conditions; 10 real swings when striking a ball and 10 practice swings without. Underpinned by the theoretical suggestions of the UnControlled Manifold (UCM) approach (Scholz & Schöner, 1999), motor control was assessed using intraindividual movement variability. Results showed the level of equivalence to be inconsistent on both an inter and intraindividual basis. Coaches should, therefore, recognize that practice swings do not share the same effect for every golfer. Optimal coaching needs to consider individual responses before committing to specific training designs if counterproductive training is to be avoided.